Socially Causal Deterministic Analysis that Causes Criminal Liability in Era 4.0 - Hisam Ahyani; Muhammad Ghofir Makturidi; Ayi Yunus Rusyana (Sociometry Journal of Social Science, Art and Humanity, 2021)
Crime and punishment in the 4.0 era are 1) a behavior, 2) a type of social phenomenon in interactions that are built between humans, 3) natural and social phenomena, 4) including interactions between people in social life, 5) considered as a process deterministic mechanics based on the law of causality. So that nowadays the study of crime and punishment in the 4.0 era needs to be developed in order to realize national development. This research method is a normative research where causal deterministics in era 4.0 are aimed at sentencing and are not only based on the concept of retributive justice alone, but also on the principle of benefits generated in the sense of aiming to prevent the recurrence of similar crimes and thereby create order and national security. The results of the study indicate that crime and punishment against socially causal deterministic challenges that lead to criminal liability in the 4.0 era is a necessity as Satjipto Rahardjo revealed that law always evolves following human development and follows the needs and values that live in humans to realize social justice for people. all Indonesian citizens, especially for society 5.0, especially in terms of digitalization through modern law as a new and renewable breakthrough and making legal paradigm changes according to the demands of the times.